Image Enhancement Model Using Dehazing Algorithm Application (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Image enhancement and classification of hazy images are widely important at various aspects.Noise removal and blur removal play a vital role in medical and imaging concepts all over the world. Detection and treatment of viral infections, genetic problems, diagnostic confirmation and multiple disorder classifications in the medical domain, finding abundant resource generators and crime scene identification in analytic prospects. In such scenarios, theimage enhancement patterns form a major crux. Several aspects have to be taken care whilst classifying and dehazing the images to perform a complete clear image with the properties matching to the original content.Dehazing algorithms has been the technical epitome of modern times. This paper deploys Haze Removal in images using dehazing and image segmentation. MATLAB image processing is being used in the paper.